Spironolactone for the treatment of acne in women, a retrospective study of 110 patients - J.W. Charny, BS; J.K. Choi, MD, PhD; W.D. James, MD (Wolters Kluwer, 2017)
Background: There is limited evidence on the safety and efficacy of spironolactone in the treatment of women with acne. Thus, for many dermatologists spironolactone remains an alternative rather than a mainstay treatment for female patients with acne. Methods: An electronic medical records search tool was used to select data from a group of women who received spironolactone to treat acne and were evaluated with the comprehensive acne severity scale (CASS) before treatment and at all follow-up visits. Data points were collected for CASS scores at each follow-up visit, concurrent and previous treatments, and side effects. These data points were used to draw conclusions about the safety and efficacy of spironolactone in this patient population. Results: There were 110 patients that met all eligibility requirements. Of these, 94 patients saw an improvement in their CASS score and 61 patients completely cleared their score to 0. There were 16 patients who did not improve and six who relapsed after initial improvement. The women saw an average improvement in their acne by 73.1% for the face, 75.9% for the chest, and 77.6% for the back. Fifty-one women experienced side effects, but only six found them bothersome enough to stop taking spironolactone. Conclusion: A majority of women in this study saw a dramatic improvement in their acne while treated with spironolactone. There were low rates of relapse or discontinuation of the medication. To further promote the use of spironolactone as a first-line systemic treatment for women with acne, there must be more prospective controlled trials. Keywords: acne, spironolactone, comprehensive acne severity scale, CASS